Acceptability of Physician Directed Academic Detailing to Increase Colorectal Cancer Screening: an Application of the RESPECT Approach - Gwen Lawson; Corey H. Basch; Patricia Zybert; Randi L. Wolf; Charles E. Basch (Tabriz University of Medical Sciences, 2015)
Background: In developing effective interventions to increase colorectal cancer (CRC) screening in at risk populations, a necessary first requirement is feasibility. This paper describes how the RESPECT approach to health education guided the conceptualization and implementation of physician-directed academic detailing (AD) to increase practice-wide CRC screening uptake. Methods: Physician-directed AD was one intervention component in a large educational randomized controlled trial to increase CRC screening uptake. Study participants, primarily urban minority, were aged 50 or older, insured for CRC screening with no out-of-pocket expense and out of compliance with current screening recommendations. The trial was conducted in the New York City metropolitan area. Participants identified their primary care physician; 564 individuals were recruited, representing 459 physician practices. Two-thirds of the physician practices were randomized to receive AD. The RESPECT approach, modified for AD, comprises: 1) Rapport, 2) Educate, but don't overwhelm, 3) Start with physicians where they are, 4) Philosophical orientation based on a humanistic approach to education, 5) Engagement of the physician and his/her office staff, 6) Care and show empathy, and 7) Trust. Feasibility was assessed as rate of AD delivery. Results: The AD was delivered to 283 (92.5%) of the 306 practices assigned to receive it; 222/283 (78.4%) delivered to the doctor. Conclusion: The AD was feasible and acceptable to implement across a range of clinical settings. The RESPECT approach offers a framework for tailoring educational efforts, allowing flexibility, as opposed to strict adherence to a highly structured script or a universal approach.